2004
DOI: 10.1139/b03-124
|View full text |Cite
|
Sign up to set email alerts
|

Within-tree variations in shoot differentiation patterns of 10 tall tree species in a Japanese cool-temperate forest

Abstract: The relations of leaf–stem balance, stem thickness, leaf thickness, and leaf size to stem length of current-year shoots were compared between terminal and lateral shoots in saplings of 10 tall tree species in a Japanese cool-temperate forest. Six monopodial and four substitution sympodial branching species were studied. For both terminal and lateral shoots, the ratios of leaf area / stem length, leaf mass / stem mass, and leaf number / stem length were greater in shorter current-year shoots, implying shoot dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
2
11
1
1
Order By: Relevance
“…Many woody species show differentiation between long and short shoots (Caesar and MacDonald 1984;Jones and Harper 1987;Miyazawa and Kikuzawa 2004;Wilson 1991;Yagi 2004). Long shoots function to expand the crown and explore new space through high investment in elongation growth.…”
Section: Linking Spatial and Temporal Strategies At The Shoot Levelmentioning
confidence: 99%
“…Many woody species show differentiation between long and short shoots (Caesar and MacDonald 1984;Jones and Harper 1987;Miyazawa and Kikuzawa 2004;Wilson 1991;Yagi 2004). Long shoots function to expand the crown and explore new space through high investment in elongation growth.…”
Section: Linking Spatial and Temporal Strategies At The Shoot Levelmentioning
confidence: 99%
“…For example, Yagi (2004) has found that the ratio of leaf number per stem length is intraspecifically greater in short current-year shoots than in long ones in 10 tall tree species. Such phenomena have been attributed to the difference in the strength of apical dominance between short and long shoots (Yagi and Kikuzawa 1999;Yagi 2000). Long stems tend to have a stronger apical dominance than short ones, and lateral buds are more likely to be suppressed.…”
Section: Effect Of Ldr On Leaf Size Leaf Number Per Stem Length Andmentioning
confidence: 99%
“…On the one hand, since only thick twigs can physically and physiologically support large leaf area and mass, stem diameter of a twig (but not stem length) is positively correlated with both individual leaf size and total leaf area supported by the twig (White 1983a(White , 1983bAckerly and Donoghue 1998;Brouat et al 1998;Preston and Ackerly 2003;Westoby and Wright 2003;Sun et al 2006;Yang et al 2009). Previous studies have shown that leaf number per unit stem length decreases with increasing stem length of currentyear shoots, both intraspecifically and interspecifically (Yagi and Kikuzawa 1999;Yagi 2000), and that leaf number per unit twig mass decreases with increasing twig size . Thus, considering the positive correlation between stem length and stem diameter in whole plants, we can expect that stem diameter and stem length would be pos-itively correlated with leaf size but negatively associated with leaf number per stem mass or length across species within twigs.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, flush and intermediate types were observed. d Branching of each species was determined by seasonal observation of tree specimens, and was based on the types reported by Kikuzawa (1983) and Yagi (2004 …”
Section: Timing Of Wide Vessel Lignificationmentioning
confidence: 99%